Potential of Microreactors for Heat Transfer Efficient co2 Methanation - Fuentes-Pereira, I (Elsevier Ltd, 2023)
The heat transfer efficiency during CO2 methanation is studied by analyzing the diffusion and advection processes inside a microreactor channel. Analytical models are obtained by solving the multidimensional transient heat balance under diffusion control to calculate the time to reach the stationary state, and to establish the conditions that favor the fastest responses. Then, the effect of advective forces (gas velocity) and channel dimensions on this time are considered a more detailed geometric configuration, allowing us to stablish the conditions to achieve isothermality in the entire domain within the microchannels. When diffusive forces dominate in the heat balance, the isothermal condition is fulfilled throughout the internal domain of the channel; however, in the presence of significant advective forces, the isothermallity is not easily fulfilled. Thus, the small microreactor dimensions make it possible to ensure an isothermal domain and achieve faster responses up to the stationary temperature. Furthermore, the thickness of the metallic wall limits the dynamic behavior of the temperature. This study confirms the advantages of process intensification in response times and isothermal condition of this reaction in this type of reactor. © 2023